HK-OxVPS: an adaptation of the Oxford Visual Perception Screen for the Cantonese speaking population in Hong Kong - Loh, Tsz Ying Flora; Vancleef, Kathleen (Frontiers in Neurology, 2025)
The Oxford Visual Perception Screen (OxVPS) is a screening tool recently developed for visual perception deficits that occur after a stroke, such as difficulties in recognizing objects, faces, and reading. The OxVPS allows for quick and accessible screening through 10 subtests, including naming pictures and matching shapes. Hong Kong has many stroke survivors, but only the wealthy can afford comprehensive cognitive assessments, highlighting the need for affordable screening tools in public healthcare. This study developed the Hong Kong—Oxford Visual Perception Screening test (HK-OxVPS), a translation and cultural adaptation of the OxVPS. Normative data from the Hong Kong neurologically healthy population was collected, and cut-off scores for each subtest were derived from the distribution of scores from 95 native Cantonese-speaking participants (50–95 years old). Comparison of cut-off scores with the cut-off scores of the UK version of the OxVPS found a general trend for lower scores on the HK-OxVPS, even on non-linguistic and non-culturally relevant subtests (intercept in Delta plot analysis = 5.69). Age, education, and visual acuity were not significant influencers of HK-OxVPS test performance (p-values 0.96, 0.16, and 0.07, respectively). However, qualitative inspection of patterns in the data of participants who were unable to complete specific subtests suggested a relationship between age and education on subtest completion. Further validity and reliability testing, as well as improvements to increase test completion, may be necessary to ensure suitability for use with Cantonese speaking stroke survivors.